Generating attribute grammar-based bidirectional transformations from rewrite rules - Fernandes, João Paulo (2014)
Higher order attribute grammars provide a convenient means for specifying uni-directional transformations, but they provide no direct support for bidirectional transformations. In this paper we show how rewrite rules (with non-linear right hand sides) that specify a forward/get transformation can be inverted to specify a partial backward/put transformation. These inverted rewrite rules can then be extended with additional rules based on characteristics of the source language grammar and forward transformations to create, under certain circumstances, a total backward transformation. Finally, these rules are used to generate attribute grammar specifications implementing both transformations.